Kultura różnorodności i kreatywności czy monotonia procesów i kultura służebności? Analiza charakterystycznych cech kultury organizacyjnej Centrów Usług Wspólnych korporacji transnarodowych - Maria Niewierko (Studia i Materiały)
Poland is the European center of specialized, outsourced competences and services, an example of which is the growing number of Shared Service Center (SSC) of transnational corporations in Poland. One of the factors that influence the quality and nature of the work in SSCs is their organizational culture. The objective of the article is to get to know the characteristic features and manifestations of SSC organizational culture, which is crucial to understanding the specificity of the work in SSCs. The article is theoretical and practical. Due to the multifaceted and definitional complexity of the organizational culture, the theory in the theoretical part was organized in such a way that four areas of its analysis were defined. In the practical part, the analysis of the characteristic features and manifestations of the organizational culture of Shared Service Centers, as well as its relationship with the parent company (headquarters), was carried out on the basis of the conducted empirical research.